Evaluasi Proses Pembukaan Kantor Cabang Mandiri Mitra Usaha (Cabang MMU) Studi Kasus di Bank Mandiri - , Aditya Sidi Pramono, Dr. Ike Janita Dewi, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Through this Thesis, the process and basic guidance of opening Mandiri Mitra Usaha Branch (MMU Branch) are explained. This is to avoid incidences of relocating or closing Branch offices since they are related to the Bank reputation. In addition, the example of successful Branch Offices as well as the less successful Branch Offices is also explained. In accordance with Bank Indonesia Regulation (PBI) number 11/1/DPNP/2009 on Public Bank, all banks which are going to perform opening, status changes, address relocation, and/or network closing of the Bank office including Regional Office, Branch Office, Sub-Branch Office, Functional Office, Cash Office, an/or Cash Service activities are obliged to list such plans in the Bank Business Plan (RBB) in the Office Network Change Plan section. A location within a traditional market is not always good. In determining the location, we also have to consider the number of the competing Banks. Location determination should be accurate and through an adequate analysis since it should not be speculated. Such speculation may cause a Branch Office to be considered failed and relocated. Supervision to the loan customers should be more strict both from daily or monthly collection using handheld is done to maintain the credit collectibility and improve the return rate and supervisory system.